Extracting Robust Biomarkers From Multichannel EEG Time Series Using Nonlinear Dimensionality Reduction Applied to Ordinal Pattern Statistics and Spectral Quantities - Kottlarz, Inga; Berg, Sebastian; Toscano-Tejeida, Diana; Steinmann, Iris; Bähr, Mathias; Luther, Stefan; Wilke, Melanie; Parlitz, Ulrich; Schlemmer, Alexander (Frontiers in Physiology, 2021)
In this study, ordinal pattern analysis and classical frequency-based EEG analysis methods are used to differentiate between EEGs of different age groups as well as individuals. As characteristic features, functional connectivity as well as single-channel measures in both the time and frequency domain are considered. We compare the separation power of each feature set after nonlinear dimensionality reduction using t-distributed stochastic neighbor embedding and demonstrate that ordinal pattern-based measures yield results comparable to frequency- based measures, and outperform them if applied to raw data. Our analysis yields no significant differences in performance between single-channel features and functional connectivity regarding the question of age group separation.